Postmortem MR in termination of pregnancy for central nervous system (CNS) anomalies. (31st December 2023) - De Keersmaecker, Bart; Dendas, Wendy; Aertsen, Michael; De Catte, Luc
Abstract: Objectives: To evaluate the concordance of conventional autopsy (CA) and postmortem magnetic resonance (MR) after termination of pregnancy (TOP) in fetuses with prenatally detected central nervous system (CNS) anomalies. Second, to determine the most informative postmortem investigation in parental counseling. Methods: All TOPs between 2006 and 2016 with prenatally detected CNS involvement and having a postmortem MR and CA as postmortem examinations were retrospectively analyzed and concordance levels were established. Results: Of 764 TOPs, 255 cases had a CNS anomaly detected prenatally (33.4%). Fetal genetic anomalies ( n = 40) and cases without both postmortem MR and CA were excluded, leaving 68 cases for analysis. Disagreement between postmortem MR and CA was observed in 22 cases (32.4%). In eight cases (11.8%), more information was obtained by CA compared with MR. However, only two cases with major additional findings were found when compared with prenatal diagnosis. In 14 cases (20.6%), MR was superior to CA either because of additional cerebral anomalies undetected by CA ( n = 5) and/or because of severe autolysis hindering pathology of the CNS ( n = 9). Conclusions: Our data point out that an adequate postmortem evaluation, valuable in parental counseling, can be provided by a postmortem MR in 97% of the cases. Key Points: An adequate postmortem evaluation, valuable in parental counseling, can be provided by a postmortem (PM) magnetic resonance (MR) in the majority of cases. PM MR is an excellent postmortem imaging tool for the brain. In cases with brain autolysis, PM MR is often the only informative PM investigation tool. PM MR is an essential adjunct to CA in the PM evaluation of pregnancies terminated for a central nervous system (CNS) anomaly.